Pharmacokinetic assessment of vancomycin in critically ill patients and nephrotoxicity prediction using individualized pharmacokinetic parameters - Ghasemiyeh, Parisa; Vazin, Afsaneh; Zand, Farid; Haem, Elham; Karimzadeh, Iman; Azadi, Amir; Masjedi, Mansoor; Sabetian, Golnar; Nikandish, Reza; Mohammadi-Samani, Soliman (Frontiers in Pharmacology, 2022)
Introduction: Therapeutic drug monitoring (TDM) and pharmacokinetic assessments of vancomycin would be essential to avoid vancomycin-associated nephrotoxicity and obtain optimal therapeutic and clinical responses. Different pharmacokinetic parameters, including trough concentration and area under the curve (AUC), have been proposed to assess the safety and efficacy of vancomycin administration. Methods: Critically ill patients receiving vancomycin at Nemazee Hospital were included in this prospective study. Four blood samples at various time intervals were taken from each participated patient. Vancomycin was extracted from plasma samples and analyzed using a validated HPLC method. Results: Fifty-three critically ill patients with a total of 212 blood samples from June 2019 to June 2021 were included in this study. There was a significant correlation between baseline GFR, baseline serum creatinine, trough and peak concentrations, AUCτ, AUC24h, Cl, and Vd values with vancomycin-induced AKI. Based on trough concentration values, 66% of patients were under-dosed (trough concentration <15 µg/ml) and 18.9% were over-dosed (trough concentration ≥20 µg/ml). Also, based on AUC24h values, about 52.2% were under-dosed (AUC24h <400 µg.h/ml), and 21.7% were over-dosed (AUC24h >600 µg.h/ml) that emphasizes on the superiority of AUC-based monitoring approach for TDM purposes to avoid nephrotoxicity occurrence. Conclusion: AUC-based monitoring approach would be superior in terms of nephrotoxicity prediction. Also, to avoid vancomycin-induced AKI, trough concentration and AUCτ values should be maintained below the cut-off points.